Strengthening TVET through Private Sector Engagement in Nepal - Bhattarai, Anoj (Journal of Technical and Vocational Education and Training, 2025)
The purpose of this study is to scrutinize existing legislative frameworks, policies, and the present scenario of private sector engagement in the technical and vocational education and training (TVET) in Nepal to understand their roles in developing a competitive technical and vocational workforce equipped with 21st century skills for employability. Utilizing qualitative research, the study reviews TVET-related legislative and policy documents as well as current implementation practices. Additionally, it uses Nepal as a case study to explore the tripartite relationship among the government, TVET providers, and private sector employers. It also reviews policies and plans, including the TVET Sector Strategic Plan (2023-32) and the 16th Periodic Plan, which emphasize collaboration between the government, academia and industry to create the skilled workforce. Despite efforts, the current state of TVET in Nepal, which is largely managed by CTEVT, shows minimal involvement from private sector employers compared to the government and TVET providers. Such insufficient industry engagement results in adverse impacts on graduates' employability. The study concludes urgency of effective collaboration among government, TVET providers, and private sector employers and calls for reform in legal and policy frameworks and the adoption of strategies to encourage meaningful private sector engagement in TVET. These strategies include apprenticeships, internships, and dual VET systems. This approach will not only help Nepal maintain a balanced relationship among key stakeholders but also enhance quality and relevance of TVET programs, leading to better employment opportunities for graduates and a more competitive national economy.